The pardoner's tale, and other plays - "Yates, Irene" (Heinemann Educational: 1999.)
The guided reading series texts are illustrated and carefully graded to interest pupils, as well as covering a wide range of the genres recommended by the "Framework for Teaching" document. They raise thought-provoking issues for discussion and fit 20 minute guided reading sessions.
Keywords: Children's plays, English